UPAYA MENINGKATKAN HASIL BELAJAR SISWA KELAS VII.6 DALAM PRAKTEK VOKAL MELALUI METODE TUTOR SEBAYA DI SMP NEGERI 1 PADANG GELUGUR - Eva Yulia Mariati; Syeilendra Syeilendra; Tulus Handra Kadir (FBS Universitas Negeri Padang, 2018)
Abstract This study aims to describe students' learning motivation using peer tutor method in vocal technique lesson in class VII.6 SMP Negeri 1 Padang Gelugur Pasaman Regency. This type of research is qualitative research with descriptive method of analysis through the stages of preparation, implementation and evaluation. The object of research is the students of class VII.6 SMP Negeri 1 Padang Gelugur with the number of students 30 people. The data were collected using observation, interview and documentation techniques. The results showed that the students' learning motivation has increased in presenting national compulsory songs in accordance with respiratory techniques, posture, sound formation, articulation, phrasering and resonance. Be aware of the results of this study can be concluded that the motivation of students in SMP Negeri 1 Padang Gelugur in learning vocal practice can be increased by using tutor peer method. This is evident from the results of the evaluation of learning conducted in formative tests, the value of 30 students in class VII.6 complete and satisfactory because it meets the standard value of KKM established by the school that is 75 and the average student more than score 75. Keywordl: Learning, vocals, Peer Tutor.